DO MANAGER POLICIES LEAD TO CORPORATE IDIOSYNCRATIC RISK? - Pinem, Jaren Jef Geovan; Firmansyah, Amrie (School of Accountancy, University of Agung Podomoro, 2022)
Certain manager policies can push the company to be riskier. Some of the manager's policiesinclude investment in investment opportunity sets, dividend policies and accrual policies throughaccrual earnings management. This study examines idiosyncratic risk with the three managers' policies.Tests were carried out using data from 75 food and beverage sub-sector companies listed on theIndonesia Stock Exchange from 2016 to 2020 using multiple linear regression analysis for panel data.The results suggest that investment opportunity set and accrual earnings management negatively affectidiosyncratic risk, whereas dividend policy positively affects idiosyncratic risk. This study places theinvestment opportunity set under test with idiosyncratic risk in the manager's policy framework, whichis rarely used in previous studies.